Comparative study of heat transfer characteristics of a tube equipped with X-shaped and twisted tape insert. (2020) - Paneliya, Sagar; Khanna, Sakshum; Mankad, Vishrut; Ray, Abhijit; Prajapati, Parth; Mukhopadhyay, Indrajit
Abstract: In order to investigate the effect of insert tape geometry on the heat exchanger tubes, present study compares thermal characteristic of water flowing in a tube equipped with X-tape and twisted tape. Material of the insert tapes used in the investigation is stainless steel. Thermal performance of heat exchanger tube has been analysed in terms of heat transfer rate (Q), Nusselt Number (Nu), friction factor (f). Significant enhancement in thermal performance was observed for X tape compared to twisted tape insert. Forced turbulence created due to modified geometry of tape played vital role in improvement of heat transfer rate in the tube. The X-shaped tape showed an enhancement of 1.27 times in heat transfer rate with respect to twisted tape. Computational fluid dynamics (CFD) analysis of the proposed tapes was performed to validate the obtained results.